Optimal Vehicle Routing Problem (VRP) For The Distribution Of Medical Devices By Applying The Clarke-Wright Algorithm - Hendra Cipta; May Fitriana Hasibuan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
In the current era of modernization, the development of the need for medical devices is increasing,g so that the companies need goods distribution system with criteria that have speed, safety, and convenience to distribute various kinds of products according to optimal distribution routes. The aim of this study is to overcome the problem of the distribution route for medical devices from PT Alkes Medan because the number of demand for goods varies for each consumers, vehicle capacites, delivery time limits, average speed that can be reached on certain routes and times and the existence of the different conditions of multiple trips at the customer's location. A heuristic algorithm named Clarke-Wright Algorithm is applied in this problem. This algorithm will be later provide an optimal solution to route problem in the distribution of medical devices and provide effectiveness in finding the shortest optimal route of medical device goods distributed to consumers. The optimal route will be described in the results section of this study